2002
DOI: 10.1002/jcc.10099
|View full text |Cite
|
Sign up to set email alerts
|

Macrotricyclic quaternary tetraammonium receptors: Halide anion recognition and interfacial activity at an aqueous interface. A molecular dynamics investigation

Abstract: We report a molecular dynamics study of the halide inclusion complexes X(-) subset L(4+) of a macrotricyclic tetrahedral receptor L(4+) built from four quaternary ammonium sites connected by six (CH(2))(n) chains. The hydrophilic/hydrophobic character of the complexes is investigated at a water/chloroform interface, represented explicitly and, despite their +3 charge and "spherical" shape, they are found to display amphiphilic behavior and to concentrate at the interface. The more lipophilic N-substituted CH(2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
21
0
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 73 publications
6
21
0
2
Order By: Relevance
“…According to simulations, smaller anions like ClO,i or quaternary ammonium NRt cations are also surface active [32], leading to a decrease in INTERFACIAL ACTIVITY OF 222 2 + 141 surface tension [51][52][53][54]. Even tetracharged tetrahedral ammonium hosts and their anion complexes are surface active, as shown by MD simulations [55], in keeping with the experimental observations of their transport properties through hydrophobic membranes [56]. The results obtained with the protonated 222 2 + cryptand agree with these features.…”
Section: Discussionmentioning
confidence: 99%
“…According to simulations, smaller anions like ClO,i or quaternary ammonium NRt cations are also surface active [32], leading to a decrease in INTERFACIAL ACTIVITY OF 222 2 + 141 surface tension [51][52][53][54]. Even tetracharged tetrahedral ammonium hosts and their anion complexes are surface active, as shown by MD simulations [55], in keeping with the experimental observations of their transport properties through hydrophobic membranes [56]. The results obtained with the protonated 222 2 + cryptand agree with these features.…”
Section: Discussionmentioning
confidence: 99%
“…22 The direct and selective detection of analytes in complicated matrix without any pretreatment is still a critical challenge in the on-site detection eld. [23][24][25] As some of the anions are basic and S 2À is the most basic with a pH of 11.7 when added to the sample at the concentration of 100 mM, we tested the inuence of pH and found that it didn't have an obvious effect on the SERS signal of paraquat in the range from 6.0 to 12.0 (Fig. Herein, we examined different common anions, and found that iodide is the most effective kind (Fig.…”
Section: Iodide-facilitated Sers Of Paraquat In Plasma or Urinementioning
confidence: 99%
“…Among the various anions, halides play an important role in environments and life [5]. Interactions between halides and synthetic receptors have been broadly investigated both experimentally and theoretically [2,[6][7][8][9][10][11][12]. Studies indicate that these interactions are mainly attributed to hydrogen bonding and electrostatic attractions.…”
Section: Introductionmentioning
confidence: 99%